Seismic survey on an open pingo system in Adventdalen Valley, Spitsbergen, Svalbard. Issue 1 (1st July 2017) - Rossi, Giuliana; Accaino, Flavio; Boaga, Jacopo; Petronio, Lorenzo; Romeo, Roberto; Wheeler, Walter
ABSTRACT: We present the results of a seismic survey on an open‐system pingo, the Innerhytta pingo, located in the Adventdalen Valley, Spitsbergen Island of the Svalbard Archipelago, Norway. To evaluate the temporal evolution of the permafrost, we need detailed knowledge of its heterogeneities, of which pingos are the most visible markers. The seismic velocity contrasts and inversions peculiar to these features can be a problem for a successful seismic survey. The present paper focusses on the limits and benefits of various seismic methods for imaging the subsurface structure of the pingo, with the aim of defining the best practice for shallow seismic exploration. We performed several tests, using classical reflection/refraction arrays, seismic tomography, and surface wave analysis. We tested different kinds of seismic sources and receivers. The combined use of several sources and receivers sets and patterns, and the use of surface wave analysis and body wave tomography allowed constructing a three‐dimensional model of the velocities. For this particular pingo, beneath an approximately 15‐m thick high‐velocity layer, low velocities are found to be present at an anomalously shallow depth. This low‐velocity layer is interpreted to host the ground water circulation that controls the pingo's structural evolution. Such observations suggest feeding water flow from depth rather than from the near surface, as commonly supposed for open‐system pingos.